Analisis Risiko Pencemaran Bahan Toksik Timbal (Pb) pada Sapi Potong di Tempat Pembuangan Akhir (TPA) Sampah Jatibarang Semarang - Wardhayani, Sutji; Setiani, Onny; Hanani D., Yusniar (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACT Background: Final waste disposal site in Jatibarang represent accumulative site of various waste from various activities in Semarang city and its surroundings. It may become an environmental contamination sources, such as air, water, land contamination, and also in living organism. The contamination substance that generally exists in the waste disposal site is toxic substance, such as lead (Pb). The disposal site in Jatibarang is used as pasturing site for beef cattle. The beef cattle consumed the organic disposal and leachate as food sources. By consuming the organic disposal and leachate from the area, the cattle may be contaminated from toxic substance (for example, Lead) that can be distributed to all part of the body of the cattle. If human being consume the meat of cattle, the body maybe contaminated by toxic substance. It may couse an adverse effect since it is accumulated in the body. Lead (Pb) may cause erythrocytes, and kidney degenerative, disorder on reproduction system, nerve system, stimulate cancer and IQ degradation. The objective of this  research was  to analyze the risk of toxic substance contamination from lead on beef cattle at  waste disposal site Jatibarang Semarang. Methods: This Study was a survey research with a cross sectional approach. Total sample of beef cattle (41, 6 samples) were taken from disposal site and  3 samples of leachate were taken from waste disposal site Jatibarang Semarang. Data were analysed using AAS for  laboratorium examination and also observation of the site. The data obtained was  analyzed by partial correlation analysis (to know the correlation between independent variable and dependent variable) Results: Analysis showed that there was significant correlation between Pb concentration in waste and Pb concentration in cattle urine  p = 0,865 r = 0,0281 old disposal (unorganic disposal that has been serapped by the cattle) p = 0,427 r = 0,1309, leachate (cattle drinking water) p = 1,000 r = 0,0001, cattle’s weight p = 0,0001 r = 0,8114, cattle’s age p = 0,0001 r = 0,7049.The conclusion of this  research is that independent variable such as Pb has in waste correlation  in waste with risk contamination of lead in beef cattle at waste disposal site Jatibarang. Keywords: lead contamination, beef cattle, final waste disposal site